The role of teachers' emotion regulation in teaching effectiveness: A systematic review integrating four lines of research - Aldrup, Karen; Carstensen, Bastian; Klusmann, Uta (Educational psychologist, 2024)
Theoretical perspectives emphasize the relevance of teachers managing their emotions for positive teacher-student interactions and student outcomes (i.e., teaching effectiveness). Four largely distinct lines of research inspired by (1) Gross' process model of emotion regulation, the concepts of (2) coping, (3) emotional labor, and (4) emotional intelligence have tested this assumption empirically. Yet, the use of different terminology complicates reviewing the current state of knowledge. Thus, we suggest a theoretical integration and synthesize evidence across research traditions. A systematic literature search resulted in 68 relevant records. We identified typically adaptive external and internal strategies as well as expressive regulation and general regulation ability as the most prominent research topics across traditions. Our results revealed mostly negative relations between expressive regulation and teaching effectiveness, but in some instances expressive regulation appeared beneficial. We also found evidence of a positive correlation between teachers' external and internal regulation and their effectiveness, but most of these studies relied on teacher self-report questionnaires, hence, these results require cautious interpretation. In studies that went beyond teacher self-assessment and relied on student reports, classroom observations, or tests, general regulation ability also did not appear related to teaching effectiveness. Implications for theory and avenues for future research are discussed.